2020
DOI: 10.1109/access.2020.3021027
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Hierarchical Control Method for Microgrid Considering Generation Cost

Abstract: Many power distribution methods of microgrid (MG) are all limited by fixed structure of MG and mathematical model, which will be out of effect once the structure changes. In order to solve the above problems, this paper proposed an adaptive hierarchical control method considering generation cost. Firstly, the distributed generators (DGs) of MG are considered as multi-agent system, and the secondary controller based on finite-time theory is constructed. Secondly, the improved gray wolf optimization (IGWO) algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The rate of change of frequency (RoCoF) and voltage (RoCoV) are also taken into consideration in the control system for ensuring stability as shown in Eqs. (24), and (25).…”
Section: Droop Control With Pll Control Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The rate of change of frequency (RoCoF) and voltage (RoCoV) are also taken into consideration in the control system for ensuring stability as shown in Eqs. (24), and (25).…”
Section: Droop Control With Pll Control Techniquementioning
confidence: 99%
“…Moreover, the improved algorithm is used for solving placement and sizing of electrical energy storage system in MGs. The IGWO is employed to dynamically optimize the rated power of Distributed Generation (DG) of the tertiary controller 25 . Salp Swarm Inspired Algorithm (SSIA) is used to improve the dynamic response and power quality of an islanded microgrid 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In [92], to reduce the generation cost of the hierarchical control system, authors proposed tertiary control based on an improved grey wolf algorithm to regulate active and reactive power of DG output. In [93], the authors proposed adaptive distributed averaging integral control to achieve economic optimization in tertiary control, which provides better flexibility for changing the DG output.…”
Section: Traditional Tertiary Controlmentioning
confidence: 99%
“…Khatibzadeh et al [16] studied the voltage stability in microgrids, applied a multi-agent control framework to control distributed flexible assets, and demonstrated that such a control ensures voltage and frequency stability in a microgird where end-consumers exchange energy. Ma and Zhang [17] applied an adaptive hierarchical control strategy considering grid stability as a constraint while minimizing the power generation costs in a microgrid with multiple prosumers. Martinez et al [18] proposed a learning-based management approach for a microgrid with competitive agents (i.e., each representing a distributed flexible asset), which improves voltage quality via reactive power-sharing between distributed generators.…”
Section: Related Workmentioning
confidence: 99%